Comparative Study on Employee Engagement and Job Satisfaction Level between Generation X and Y - Yesica Apriliana Paska (Journal of Management and Business Environment (JMBE), 2023)
The purpose of this research is to compare the level of employee engagement and job satisfaction of the generations X and Y in the Human Capital General Affairs Division of PT. Karoseri. This type of research is a comparative descriptive study intended to examine differences the level of employee engagement and job satisfaction. The population of this study was all employees of the Human Capital General Affairs Division with a total of 35 people. They are all used as the sample. The data analysis techniques were descriptive analysis, inferential analysis, and t-test which was used for comparison. The results showed that there was no difference in the level of employee engagement and job satisfaction between the generation X and Y. High level of employee engagement indicates that the two generations have already had feeling to engage with the company. Moderate level of job satisfaction indicates that the generation X and Y were quite satisfied with their current job.